2021
DOI: 10.3390/children8111041
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Red Blood Cell Distribution Width, Mean Platelet Volume and Platelet Distribution Width in Children with Acute Appendicitis

Abstract: Background and Objectives: Acute appendicitis in pediatric patients is one of the most common surgical emergencies, but the early diagnosis still remains challenging. The aim of this study was to determine the predictive value of Red blood cell distribution width (RDW), Mean platelet volume (MPV) and Platelet distribution width (PDW) in children with acute appendicitis. Materials and Methods: This study was a retrospective assessment of laboratory findings (RDW, MPV, PDW) of patients who underwent surgical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
3
9
0
1
Order By: Relevance
“…While reduced values of this parameter have no major clinical significance, elevated values may indicate destruction and, at the same time, production of new, smaller platelets, because the acute phase inflammatory reactants lead to megakaryopoiesis. 19 , 24 Our research confirmed statistically significantly higher values of this parameter compared to the control group. Shankaralingappa et al reported that PDW was significantly higher in those with COVID‐19 than non‐COVID‐19 controls, and could be used as an additional inflammatory marker.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…While reduced values of this parameter have no major clinical significance, elevated values may indicate destruction and, at the same time, production of new, smaller platelets, because the acute phase inflammatory reactants lead to megakaryopoiesis. 19 , 24 Our research confirmed statistically significantly higher values of this parameter compared to the control group. Shankaralingappa et al reported that PDW was significantly higher in those with COVID‐19 than non‐COVID‐19 controls, and could be used as an additional inflammatory marker.…”
Section: Discussionsupporting
confidence: 80%
“…PDW is a platelet index that indicates their size distribution in percentage. While reduced values of this parameter have no major clinical significance, elevated values may indicate destruction and, at the same time, production of new, smaller platelets, because the acute phase inflammatory reactants lead to megakaryopoiesis 19,24 . Our research confirmed statistically significantly higher values of this parameter compared to the control group.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…One of the most commonly used laboratory parameters when considering the diagnosis of acute appendicitis is the number of leukocytes. Some authors state that the number of neutrophils is a far more sensitive parameter and that neutrophil to lymphocyte ratio can be a useful predictor of complicated appendicitis forms [15,16]. A significant percentage of our subjects (83.64-95.24%) had leukocyte values greater than 10 × 10 9 /L, which is consistent with the diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…Some studies have shown that high RDW levels can be seen in various pathological conditions. However, in studies on the differential diagnosis of AA and determining the severity of appendicitis in children, a superiority of RDW over other parameters has not been demonstrated [17,18]. In studies conducted on adults, RDW was not found to be significant in the differential diagnosis between AA and ureteral Stones [8,9].…”
Section: Discussionmentioning
confidence: 99%